Effect of sowing date and row spacing on phenology and yield of two diverse genotypes of pigeonpea (Cajanus cajan) - PATEL, N R; MEHTA, A N; SHEKH, A M (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted to investigate the effect of sowing date (30 June, 20 July and 9 August) and row spacing (60 and 90 cm) on the phenology and yield of 2 diverse pigeol1pea [Cajannus cajan (L.) Millsp.] genotypes (GT 100’ and ’BDN 2’). A delay in sowing frOID 30 June substantially reduced the time taken to flower-bud initiation and maturity in both the genotype. Both these characters were largely int1uenced by prevailing temperature and rainfall distribution. Pigeonpca sown on 30 June gave significantly higher seed yield and total biomass than that sown late.’GT 100’, having early maturity and determinate growth habit, was found superior to the long-duration genotype ’BDN 2’. The narrow row spacing (60 cm) led to higher plant population, which could not be compensated by increased yield attributes under wide row spacing (90 cm). Thus ’GT 100’ sown on 30 June in 60 cm apart rows is promising for sole pigconpea cultivation due to increased yield attJibutes under rainfed condition of central Gujarat.